Efficacy and Temporal Dynamics of Genicular Nerve Block in Primary and Secondary Knee Osteoarthritis for Pain and Function: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li Z; Bai Y; Liu C; Gu Y (Journal of Pain Research, 2025)
Ziqing Li,1 Yang Bai,2 Cheng Liu,2 Yanglin Gu1 1Nanjing Medical University Affiliated Wuxi No.2 People’s Hospital, Jiangsu, People’s Republic of China; 2Jiangnan University Affiliated Wuxi No.2 People’s Hospital, Jiangsu, People’s Republic of ChinaCorrespondence: Yanglin Gu, Nanjing Medical University Affiliated Wuxi No.2 People’s Hospital, Email 13525000870@163.comPurpose: Genicular nerve block (GNB) has emerged as a promising intervention for knee osteoarthritis (KOA), yet its comparative efficacy remains incompletely understood. The purpose of this review was to assess the effectiveness of GNB in reducing pain and improving function for primary or secondary KOA.Methods: We conducted systematic searches of PubMed, Web of Science, and Embase up to October 9, 2024, for randomized controlled trials comparing GNB with other therapies. The data were analyzed using Review Manager (RevMan) 5.4, and study quality was assessed using the Cochrane risk of bias tool.Results: This study included six RCTs involving a total of 420 participants. Results revealed that GNB significantly reduced pain (SMD = 1.00, 95% CI: 0.48– 1.52, p=0.0002) and improved function (SMD = 1.07, 95% CI: 0.37– 1.77, p=0.003) compared to other interventions. Subgroup analyses showed that GNB provided better pain relief at 2 weeks (SMD=1.21; 95% CI: 0.09– 2.33; P=0.03) and greater functional improvement at 12 weeks (SMD=1.13; 95% CI: 0.10– 2.16; P=0.03).Conclusion: This review suggested GNB as an effective intervention for KOA management, with distinct temporal patterns for pain relief and functional improvement.Keywords: knee pain, genicular nerve block, knee osteoarthritis, meta-analysis